Philosophy and Management in China: An Historical Account - Yan, Li; Hafsi, Taïeb (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2015)
Chinese organizational behavior is the product of history. In this paper, we propose an introduction to the philosophical bases of Chinese behavior. This introduction is contextualized and historically situated; then compared to Western thinking to ensure that its value for organizations is understood. We examine first the dominant Chinese philosophy schools and decode their possible meaning for managing organizations. In particular, such issues as organizational structure, leadership, emotions and time-orientation are discussed in reference to traditional values. The paper’s conclusion suggests that Chinese firms’ behavior can be better understood and studied by looking at their philosophical and historical roots.